Biparental care behaviour of captive Ringed Teal Callonetta leucophrys - Brewer, Gwen (Wildfowl, 1989)
Parental care behaviour was observed in three captive families of Ringed Teal. Both parents were very protective of their broods and performed distraction displays to lead people away from their ducklings. Males were more active than females in chasing other birds away from the ducklings. Only females brooded the young. Males frequently perched on lookouts while the female and ducklings fed. Male parents retrieved lost or lagging ducklings more often than female parents although the female usually led the brood. Family members greeted each other when they reunited after brief separations and generally formed a cohesive group. One pair renested when their first brood was 24 days old and the male cared for these ducklings while the female incubated the second clutch. This observation and others suggest that male parental care may contribute to a strategy of double brooding in this species.